Identification of Patients with Microscopic Hematuria who are at Greater Risk for the Presence of Bladder Tumors Using a Dedicated Questionnaire and Point of Care Urine Test - A Study by the Members of Association of Urooncology, Turkey - (:unkn) unknown (ASIAN PACIFIC ORGANIZATION CANCER PREVENTION, 2014)
In patients with microscopic hematuria there is a need for better identification of those who are at greater risk of harbouring bladder tumors. The RisikoCheck (c) questionnaire has a strong correlation with the presence of urothelial carcinoma (UC) of the bladder and in combination with other available tests may help identify patients who require detailed clinical investigations due to increased risk of presence of bladder tumors. This study aimed to evaluate the efficacy of RisikoCheck (c) questionnaire together with NMP-22 (R) (BladderChek (R)) as a point-of-care urine test in predicting the presence of bladder tumors in patients presenting with microscopic hematuria as the sole finding. In this multi-institutional prospective evaluation of 303 consecutive patients without a history of urothelial carcinoma (UC), RisikoCheck (c) risk group assessment, urinary tract imaging and cystourethroscopy as well as urine cytology and Nuclear Matrix Protein-22 (NMP-22 BladderChek) testing were performed where available. The sensitivity, specificity, negative predictive value (NPV), and positive predictive values (PPV) for the risk adapted approach were calculated. All patients underwent cystoscopy, and tumors were detected in 18 (5.9%). Urine cytology and NMP-22 was positive for malignancy in 9 (3.2%) and 12 (7.5%) of patients, respectively. A total of 43 (14%) patients were in the high risk group according to the RisikoCheck (c) questionnaire. The sensitivity and specificity of the questionnaire in detecting a bladder tumor was 61.5 % and 84.0 % in the high risk group. In patients with either a positive NMP-22 test or high risk category RisikoCheck (c), 23.6% had bladder tumors with a corresponding sensitivity of 54.2% and specificity of 88.6%. If both tests were negative only 3.3% of the patients had bladder tumors. The results of our study suggest that the efficacy of diagnostic evaluation of patients with microscopic hematuria may be further enhanced by combining RisikoCheck (c) questionnaire with NMP-22.
Keywords: Microscopic hematuria; bladder neoplasms; RisikoCheck (c); NMP-22; bladder check; CANCER; DIAGNOSIS; ADULTS; RECOMMENDATIONS; GUIDELINE; AUA